Chromosome 11q13 amplification correlates with poor response and prognosis to PD-1 blockade in unresectable hepatocellular carcinoma - Yan, Kai; Zhang, Ding; Chen, Yanan; Lu, Wenfeng; Huang, Mengli; Cai, Jinping; Chen, Shiqing; Bei, Ting; Bai, Yuezong; Lv, Jian; Fu, Yong; Zhang, Haibin (Frontiers in Immunology, 2023)
Background & aims: Little is known about molecular biomarkers that predict the response and prognosis in unresectable hepatocellular carcinoma (HCC) treated with programmed death (PD)-1 inhibitors. Methods: A total of 62 HCC patients who underwent next-generation sequencing were retrospectively included in our department for this study. Patients with unresectable disease were subjected to systemic therapy. PD-1 inhibitors intervention (PD-1Ab) group and nonPD-1Ab group included 20 and 13 patients, respectively. Primary resistance was defined as initial on-treatment progression or progression with an initial stable disease of less than 6 months. Results: Chromosome 11q13 amplification (Amp11q13) was the most common copy number variation in our cohort. Fifteen (24.2%) patients harbored Amp11q13 in our dataset. Patients with Amp11q13 showed higher level of Des-γ-carboxy-prothrombin (DCP), tumor number and were more prone to be combined with portal vein tumor thrombosis (PVTT). In the PD-1Ab group, the proportion of progressive disease (PD) in patients with Amp11q13 was significantly higher than that in patients with nonAmp11q13 (100% vs 33.3%, P=0.03). In the nonPD-1Ab group, the proportion of PD in patients with Amp11q13 and nonAmp11q13 had no significant difference (0% vs 11.1%, P＞0.99). In the PD-1Ab group, the median progression-free survival (PFS) was 1.5 months in Amp11q13 patients vs 16.2 months in non-Amp11q13 patients (HR, 0.05; 95% CI 0.01-0.45; P = 0.0003). No significant difference was observed in the nonPD-1Ab group. Notably, we found that hyperprogressive disease (HPD) might be associated with Amp11q13. The increased density of Foxp3+ Treg cells in HCC patients with Amp11q13 might be one of potential mechanisms. Conclusions: HCC patients with Amp11q13 are less likely to benefit from PD-1 blockade therapies. These findings may help guide the use of immunotherapy for HCC in routine clinical practice.